Communication Planning of Langsa City Government in Building an Islamic and Environmentally Friendly City - Syukur Kholil; Ahmad Thamrin Sikumbang; Mawardi Siregar (Budapest International Research and Critics University, 2019)
This study analyzes three points, namely: 1) communication planning conducted by the Langsa City government; 2) community participation in communication planning; and 3) the effectiveness of communication planning in realizing urban development that is Islamic and environmentally friendly. This research method is qualitative by collecting data through medalam interviews, observations and documentation studies. The results of this study: First, to create an Islamic and environmentally friendly city, communication planning conducted by the Langsa City government, namely analyzing field data, planning communication, and planning strategies implementation of communication that has been planned. Second, community participation in communication planning is directly by following Musrembang, FGD and public discussions and indirectly by representing their aspirations through council members in Langsa DPRK institution. Third, communication planning to realize the development of an Islamic and environmentally friendly Langsa City has not been effective, because the use of strengths and opportunities has not been able to be optimized to overcome the challenges of weaknesses, so the pace of development of the Langsa City has been slow.Keywords: Communication planning; Islamic cities; environmentally friendly.